Ocular Manifestations of Stevens-Johnson Syndrome - Daniar Indah Suryowati; Ratna Doemillah (Universitas Wijaya Kusuma Surabaya, 2021)
The purpose of this case report was to have a further study of the proper management of ocular manifestations caused by Stevens-Johnson Syndrome, which aims to minimize the chances of complications. This case report will discuss the ocular manifestations of Stevens-Johnson syndrome. A case report. A 4 years old girl with the problem on admission was the adhesion of her membranes layer (conjunctiva) and eyelid on both of her eyes. The patient’s family also gave additional information on the patient’s eyes problem: pain on both her eyes, tearing, discharge which came out frequently from her eyes, and a white spot in the black section of her eyes. The fluorescein test revealed a positive result, with conjunctival hyperemia. The case was treated as symblepharon and corneal erosion post Stevens-Johnson syndrome, for temporary treatment using artificial tears and antibiotic eye ointment. Ocular manifestations occur in a significant number of patients, and the most severe form of Stevens-Johnson syndrome occurs in those at the end of the spectrum. The acute phase of the disease is characterized primarily by eyelid involvement. The lids are typically swollen and erythematous. Soon after that, or coincident with this, the conjunctiva is inflamed. Conjunctivitis frequently parallels the skin findings, with bullae formation and eruption. Membrane or pseudo-membrane formation then occurs. The healing process can result in cicatricial changes, including symblepharon, ankyloblepharon, eyelid margin rotation, severe dry eye, and conjunctivilization of the cornea.